Outcomes of Whipple procedure/pancreaticoduodenectomy- an eighteen-year experience at a tertiary cancer care centre in south India - Shanmugam, Subbiah; R. R., Pravenkumar (International Journal of Research in Medical Sciences, 2024)
Background: Early postoperative mortality rates after pancreaticoduodenectomy are in the range of 2-5%. Nonetheless, morbidity rates are still at 30-50% calling for apt strategies. The goal of this study was to examine the outcomes in terms of postoperative morbidity and 30-day mortality while additionally reviewing the demographic, clinical and pathological features of patients undergoing Whipple procedure at our government institution and comparing the outcomes with literature. Methods: Data about demographic characteristics, intraoperative findings, postoperative histopathology, postoperative course, early post-operative outcomes, complications, and causes of postoperative death in patients who underwent pancreaticoduodenectomy for periampullary and pancreatic carcinoma between September 2006-August 2023 were collected and analysed. Results: 45 patients were analysed. Mortality rate was 15.6%. Seven patients died perioperatively; three from cardiac cause (myocardial infarction), two from bile leak and sepsis, one from pulmonary embolism, and one as a result of postoperative hemorrhage. The morbidity rate was 54%. The most common early postoperative complication was delayed gastric emptying (31%) followed by postoperative pancreatic fistula (22%). The median overall survival of 39 patients was 21±6.5 months. The 5-year survival was 17 months. Conclusions: Considering the fact that postoperative morbidity after Whipple procedure was similar to other centres, but the mortality rate being high, better knowledge about salvage techniques, improvements in perioperative care, use of interventional radiology, and running quality improvement projects to standardize postoperative recovery protocol could help in reducing the mortality and improve the outcome.